2018
DOI: 10.1016/j.biortech.2018.06.004
|View full text |Cite
|
Sign up to set email alerts
|

The path forward for lignocellulose biorefineries: Bottlenecks, solutions, and perspective on commercialization

Abstract: Lignocellulose biorefinery encompasses process engineering and biotechnology tools for the processing of lignocellulosic biomass for the manufacturing of bio-based products (such as biofuels, bio-chemicals, biomaterials). While, lignocellulose biorefinery offers clear value proposition, success at industrial level has not been vibrant for the commercial production of renewable chemicals and fuels. This is because of high capital and operating expenditures, irregularities in biomass supply chain, technical proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
170
0
5

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 479 publications
(175 citation statements)
references
References 83 publications
0
170
0
5
Order By: Relevance
“…This is currently mainly limited by high costs associated with the conversion of these feedstocks into fermentable sugars (Bardhan, Gupta, Gorman, & Haider, 2015). Due to technological challenges associated with utilizing second generation feedstocks, for example, during the pretreatment phase of the biomass (Biddy et al, 2016;Chen & Qiu, 2010) and related economic challenges of biochemical production from second generation biomass (Chandel, Garlapati, Singh, Antunes, & da Silva, 2018;Lynd et al, 2017), alternative feedstock sources are increasingly receiving attention. These feedstocks include engineered crops, algae, and urban residues, such as household waste (third generation feedstock; Yang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This is currently mainly limited by high costs associated with the conversion of these feedstocks into fermentable sugars (Bardhan, Gupta, Gorman, & Haider, 2015). Due to technological challenges associated with utilizing second generation feedstocks, for example, during the pretreatment phase of the biomass (Biddy et al, 2016;Chen & Qiu, 2010) and related economic challenges of biochemical production from second generation biomass (Chandel, Garlapati, Singh, Antunes, & da Silva, 2018;Lynd et al, 2017), alternative feedstock sources are increasingly receiving attention. These feedstocks include engineered crops, algae, and urban residues, such as household waste (third generation feedstock; Yang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Biorefineries initially followed oil refineries by using a single feedstock with huge processing capacities to achieve the maximum economy of scale, but the opportunities for installing such biorefineries in most rural areas in Europe, Latin American countries, and even worldwide are scarce. Studies have revealed that the main bottlenecks are associated with high capital expenditure (CAPEX) and operating expenditure (OPEX), and very often the lack of a sustainable biomass supply at regional level . Small‐scale biorefineries have been proposed as a potential solution to overcome most of these challenges because, when located in rural areas, they can promote territorial economic cohesion and generate local jobs directly and indirectly .…”
Section: Introductionmentioning
confidence: 99%
“…One possible reason for this finding is that the concept of bioeconomy is long-term in nature [58], and has not yet unleashed its full potential [25]. Another important reason may be that bioproducts have not fully hit commercialization [59], and consumers are generally unfamiliar with bio-based products [60]. Bioproducts are currently being promoted by policymakers as policymakers map up strategies [4] to realize bioeconomy dreams, but this initiative would be more successful if it was led by the market.…”
Section: Discussionmentioning
confidence: 99%